Communication channel preference for raising rabies awareness among dog owners in Thailand: A nationwide study - Wagee Worrawattanatam; Wongsaton Ektasaeng; Phakwat Pornsuksant; Sarin Suwanpakdee; Sith Premashthira; Anuwat Wiratsudakul (One Health)
Rabies is a severe zoonotic disease with potentially fatal consequences. Effective communication channels are crucial for disseminating key rabies prevention and control messages to target populations. This study examined how dog owners' demographic factors influenced communication channels in Thailand. We distributed a questionnaire survey to retrieve general demographic data of participants and the ranks of their communication channels. We used the mean ranking score to assess the most accessible and commonly used platforms. Univariate and multiple logistic regression methods were used to determine the association between each demographic feature and the preference for communication. In total, 476 participants were involved across all regions of Thailand. Village health volunteers represented the most selected channel, as identified by the mean ranking (3.32), followed by public loudspeaker (3.30) and television (2.93). Age, occupation, region, and cat ownership significantly influenced how people chose the channels. Moreover, farmers likely received information from various sources, and elderly individuals generally preferred to receive information about rabies from administrative authorities, such as village heads. These results can benefit policymakers aiming to enhance communication strategies in public health. This study enhances rabies risk communication and aligns with global health initiatives to eliminate dog-mediated rabies by 2030.